Development of Interactive Assessment CBT Based on Learning Management System in Leadership Project I Course - Hasmalena, Hasmalena; Hermawan, Rudi; Alrefi, Alrefi; Akbari, Akbari; Eprilia, Winda; Arneta, Marsela (Edukasi, 2023)
This research was arisen by the lack of an assessment in the form of test items as an interactive assessment for Computer-Based Test (CBT) based on Learning Management System (LMS). Previously, only topic-based tasks were available, particularly lacking in leadership project courses. In practice, assessment mainly relied on tasks in leadership project courses for teacher professional education students (PPG), resulting in suboptimal data collection for measurement which made educators difficult to assess or measure student performance. The research method used was Research and Development (R&D) with the Miles & Huberman model. This study aims to develop effective and efficient measurement data in the form of interactive LMS-based mechanical assessments (CBT). The research involved students who enrolled in the Leadership Project course at PPG Unsri. The research object was the measurement tool results from the collection of data from answered assessment items, to be effectively and efficiently presented in the form of interactive LMS-based mechanical (CBT) assessments. Data collection begins with observation and the creation of item grids. Data analysis techniques use the Miles & Huberman model analysis, which includes four stages: data collection, data reduction, data presentation, and drawing conclusions. Data analysis was performed using SPSS. The results of this study indicate that the product in the form of LMS-based test items (CBT) is valid and reliable as an assessment tool in leadership project courses at the Faculty of Teacher Training and Education, Universitas Sriwijaya.